Historization and Mythologization of Characters in Buryat Traditions (Image of Balzhan) - B. B. Tsybikova; L. S. Dampilova (Научный диалог)
In a comparative aspect, historical and mythological components in the main oral and written versions of stories about a woman who was the main character in the oral traditions and chronicles of the Khori-Buryats are considered. The novelty of the study is in the identification of the historical cognitive part of the traditions in the context of real events concerning the image of Balzhan. The results of a comparative analysis of different versions of written texts and oral stories to identify mythological sacred additions and transform the real story are presented. The relevance of the study is due to a comparative analysis of the main versions of tradition in an interdisciplinary aspect, which led to the conclusion that the storyline of the novels about Balzhan in the vast majority of cases develops exclusively in the context of describing the history of the formation and development of the ethnic group of the Khorinsky Buryats in the period from the 17th century. It is proved that in written versions the main oral plot outline is preserved with the strengthening of historical components, in some cases the entire mythological part is removed to create the image of a plausible historical hero. The authors note that the mythological nomadic insets in the legends go back to oral traditions, having the functions of sacralizing and heroizing the tragic fate of the non-standard woman who determined the fate of the tribe.